Complexidade tributária, ambiente de negócios e transparência: uma análise para países selecionados - Uchôa Júnior, Antônio Mauro de Souza (2021)
This dissertation investigates the impacts of the tax system on the Business Environment, Transparency and Economic Development from a sample of 100 countries in 2018. As controls for assessing the degree of complexity of the tax system, the Quantitative of Taxes were considered, the Average Time for Compliance with Tax Obligations and the maximum terms for Tax Prescription in each country. Based on this information provided by the consultancy PriceWaterHouseCoopers, by the United Nations International Transparency and by the World Bank's Doing Business report, three cross-section models were estimated following the Newey-West proposal when it was necessary to adapt the estimators to an error term heteroscedastic. Robust estimates allow us to infer that both the amount of taxes and the time to fulfill tax obligations harm the business environment, transparency and economic development of countries, while a longer statute of limitations is harmless as an object of policy or reform that impacts the aforementioned dependent variables. Together, the results confirm that the search for tax simplification proves to be a good premise to be adopted by formulators of economic policy in the tax field.